Analisis Manajemen Risiko pada UMKM Kue: Studi Kasus Karin Cake & Cookies - Khoerunnisa, Dzilla; Mutakin, Farhan Mukti; Sundari, Annisa Pratiwi; Maulana Yusuf, Rafli; Suwarna, Asep (Universitas Serambi Mekkah, 2024)
This research discusses Risk Management Analysis at UMKM Karin Cake Cookies using qualitative methods. The analysis process includes risk identification, risk assessment based on Probability and Impact, evaluation using a 3x3 matrix, and risk control. Data was obtained through direct interviews with business owners. The identification results revealed 5 types of risks faced by Karin Cake Cookies. To overcome these risks, various control strategies are implemented, such as using backup equipment, involving labor from family members as backup, and utilizing online platforms for marketing. In addition, optimal raw material storage and product innovation are important factors in facing competition and market changes. The implementation of risk management is expected to help companies minimize existing or future risks and can provide an assessment of various risks.